True stories - Byrne, David 1952-; Byrne, David 1952-; Tobolowsky, Stephen Harold 1951-; Henley, Beth 1952-; Lachman, Edward 1948-; McBride, Elizabeth; Goodman, John 1952-; McEnroe, Annie; Kurtz, Swoosie 1944- (The Criterion Collection, 2019)
Ein optisch ehrgeiziger und musikalisch vielfältiger Rockmusik-Film um die Beziehungen zwischen originellen Kleinbürgern in einem Städtchen in Texas. Statt der angestrebten "menschlichen Komödie" mit allgemeingültigen Aussagen ergibt sich wegen der Bezüge auf allzu spezielle psychische und gesellschaftliche Bedingtheiten eine nicht immer leicht verständliche, stets aber intelligent-unterhaltsame Provinzsatire. - Ab 14. [Film-Dienst]
Original: USA 1986
Director-approved Blu-ray special edition features: new, restored 4K digital transfer, supervised by director David Byrne and cinematographer Ed Lachman, with 5.1 surround DTS-HD Master Audio soundtrack, supervised by Byrne ; new documentary about the film’s production, featuring Byrne, Lachman, screenwriter Stephen Tobolowsky, executive producer Edward Pressman, coproducer Karen Murphy, fashion-show costume designer Adelle Lutz, casting director Victoria Thomas, consultant Christina Patoski, actor Jo Harvey Allen, and artist and songwriter Terry Allen ; CD containing the film’s complete soundtrack, compiled here for the first time ; Real life (1986), a short documentary by Pamela Yates and Newton Thomas Sigel made on the set of the film ; No time to look back, a new homage to Virgil, Texas, the fictional town where True stories is set ; new documentary about designer Tibor Kalman and his influence on Byrne and work on the film, featuring Byrne and artist Maira Kalman, Tibor’s widow ; deleted scenes ; trailer ; English subtitles for the deaf and hard of hearing ; plus: Essays by critic Rebecca Bengal and journalist and author Joe Nick Patoski, along with, for the Blu-ray edition, an essay by Byrne; a 1986 piece by actor Spalding Gray on the film’s production; and a selection of production photography, along with Byrne’s tabloid clippings and writing about the film’s visual motifs